Isolation of Serratia marcescens involved in chitin degradation in the bulb mite Rhizoglyphus robini - Zindel, Renate; Ofek-Lalzar, Maya; Aebi, Alexandre (My University, 2017)
There is an increasing awareness of the importance of the microbiome of arthropods to understand their host’s biology. In the bulb mite, Rhizoglyphus robini, associated bacteria have been found to be involved in its chitinolytic abilities. The bulb mite, a plant pest feeding on below- ground parts of mostly Liliaceae crops, prefers fungus- infested plants. Moreover its fitness is higher when feeding on a fungal food source than when feeding on non-infected plants. In this study we isolated a chitinolytic bacterium from mite homogenate and identified it molecularly as Serratia marcescens (Bizio 1823), which is a model organism for chitin degradation. Precise identification of the bacterium can be important for the development of biological control programs of the mite as well as for further studies investigating Serratia marcescens and its chitinolytic machinery.
Keywords: Chitinolytic activity . Biological control . Primary pest . Secondary pest . Serratia marcescens . Rhizoglyphus robini . Mite holobiont . arthropod microbiome